Second Language Sentence Stress Assignment : Self‐ and Other‐Assessment - Teló, Cesar; Kivistö de Souza; Hanna; O'Brien, Mary Grantham; Carlet, Angélica (Wiley, 2025)
Research on second language (L2) pronunciation self-assessment reports a general misalignment between self- and other-assessment. This has been attributed to the object of self-assessment, the self-assessment task, the measures to which self-assessment is compared, and speakers’ characteristics. Here, we examined self-assessment of a discrete phonological feature—sentence stress—by L2 English speakers as compared to the assessment of first language English listeners through a timed, forced-choice judgment task with low-pass filtered stimuli, which contained only suprasegmental cues. Additionally, we explored how individual differences among speakers predict self-assessment. Speakers generally overestimated their accuracy in sentence stress assignment in a pattern resembling the Dunning-Kruger effect despite the controlled nature of the task. Speakers with larger vocabulary size judged their sentence stress assignment as correct more often and showed greater overconfidence and miscalibration. Finally, the assessments of speakers with a background in applied linguistics and/or language teaching were more aligned with listeners’ assessments.